Creation of single-wing Lorenz-like attractors via a ten-ninths-degree term - Pan Jun; Wang Haijun; Ke Guiyao; Hu Feiyu (Open Physics)
In light of the subtle connection between the strange attractors and the degree of dynamical systems, in this study, we propose a new simple asymmetric Lorenz-like system and report the finding of single-wing Lorenz-like attractors, which can also be created by the collapse of asymmetric singularly degenerate heteroclinic cycles. Moreover, we prove the existence of a single heteroclinic orbit to the origin and the nontrivial equilibrium point. Besides, numerical simulations also verify the theoretical analysis.